Um ensaio sobre o direcionamento para a criação de projetos relacionados à políticas públicas - Novaes, Francisco Antonio Maciel; Andrade, Herlandí De Souza [UNESP] (My University, 2018)
There is great discussion about public policy and projects, in all spheres of government, whether at the federal, state, or municipal level. In many cases, there are resources, but not projects. This work aims to propose a step-by-step method for designing projects, based on public policies, in order to promote improvements in public management, with specific results and that contributes to the quality of life of citizens and society as a whole. everything. This research is classified as qualitative. Bibliographical research and discussions with public sector professionals were carried out. The method is a logical, interrelated proposal, constituted in steps that comprise a step by step to plan a project, from a public policy.
An essay on targeting for the creation of public policy-related projects
Keywords: Project management; Projects; Public management; Public policy